THE ANALYSIS OF MENTAL METAPHORS IN LEILA ABOULELA’S NOVEL “MINARET” - M.R.Kilicheva (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
This article examines the role of mental metaphors in Leila Aboulela’s novel Minaret, analyzing how cognitive linguistics can uncover deeper layers of meaning in the protagonist’s experiences. Through a detailed study of metaphorical expressions related to faith, displacement, and self-identity, the research highlights the cognitive mechanisms that shape the protagonist’s perception of her journey. The study draws upon Conceptual Metaphor Theory to explore how abstract emotions and cultural transformations are mapped onto concrete experiences. The findings demonstrate that Aboulela employs mental metaphors to depict the protagonist’s psychological evolution, reinforcing the novel’s themes of spiritual awakening and cultural hybridity. This analysis contributes to cognitive literary studies by illustrating how metaphor serves as a cognitive bridge between personal experience and broader socio-cultural realities.